Impact of entrepreneurial self-efficacy and entrepreneurial motivation on micro and small business success for food and beverage sector in East Java, Indonesia - Veronika Agustini Srimulyani; Yustinus Budi Hermanto (Economies, 2022)
The research aims to examine the impact of entrepreneurial self-efficacy and entrepreneurial motivation on the success of the food and beverage (F&B) sector's micro and small enterprises (MSEs). The sample was selected using purposive sampling techniques from 267 MSE owners in the F&B businesses in Madiun City, Madiun Regency, and Magetan Regency, East Java, Indonesia. The test results of the hypothesis showed that: (1) partially, self-efficacy entrepreneurship and entrepreneurial motivation are significantly positive on business success in micro and small F&B businesses in East Java, Indonesia; (2) entrepreneurial motivation acts as a partial mediation of the influence of self-efficacy entrepreneurship on the business success of micro and small businesses in the field of food and beverage in East Java, Indonesia; abd (3) simultaneously, self-efficacy entrepreneurship and the influence of entrepreneurial motivation are significantly positive on business success in micro and small businesses in the food and beverage fields of East Java, Indonesia. The results showed that self-efficacy and motivation in entrepreneurship are necessary because they affect business success, particularly in micro and small F&B businesses in Indonesia. Further research can explore other factors that influence business success by expanding the research area and other types of creative industry businesses. Further research could explore other factors influencing business success by expanding research areas, such as entrepreneurial leadership and innovative work behavior.
Keywords: 330; business success; entrepreneurial motivation; entrepreneurial self-efficacy; food and beverage